The Charter and By-Laws of the Borough of Wallingford 55 (1882) - (:unkn) unknown (My University, 1882)
§ 15: Prohibited the discharge of any pistol, gun, cannon, or other fire-arm in any street, park, or public ground. Violators fined not exceeding twenty-five dollars.
Keywords: DISCHARGE